2022
DOI: 10.3389/fvets.2022.903633
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance, biofilm formation, and virulence factors of isolates of staphylococcus pseudintermedius from healthy dogs and dogs with keratitis

Abstract: Canine bacterial keratitis is a common infection that can potentially threaten vision. Staphylococcus pseudintermedius (S. pseudintermedius) is an opportunistic pathogen that has been isolated from the canine conjunctival sac but there are only a few reports on the role of this bacterium in canine keratitis. This study focused on the distribution rate of S. pseudintermedius in the canine conjunctival sac, and the antibiotic resistance, biofilm-producing ability, and dissemination of virulence factors in strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…The proposed modes of antimicrobial actions of NAC are a competitive inhibition of the uptake of amino acids, such as cysteine, by bacterial cells or the reaction of its own sulfhydryl group with the bacterial cell proteins [ 64 , 65 ]. Human, canine and feline infectious ulcerative keratitis have also been associated with the biofilm formation of different microorganisms [ 63 , 66 , 67 , 68 ]. The complex bacterial communities are encapsulated in an extracellular polymeric matrix, and hereby, they have an increased resistance to antibiotics and the host immune response, increasing bacterial survival, which further complicates the treatment of bacterial keratitis [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed modes of antimicrobial actions of NAC are a competitive inhibition of the uptake of amino acids, such as cysteine, by bacterial cells or the reaction of its own sulfhydryl group with the bacterial cell proteins [ 64 , 65 ]. Human, canine and feline infectious ulcerative keratitis have also been associated with the biofilm formation of different microorganisms [ 63 , 66 , 67 , 68 ]. The complex bacterial communities are encapsulated in an extracellular polymeric matrix, and hereby, they have an increased resistance to antibiotics and the host immune response, increasing bacterial survival, which further complicates the treatment of bacterial keratitis [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic pheno- and genotypes have been shown to lead to the invasion of corneal cells and concurrent corneal ulcerations [ 62 ]. Wang et al also showed that the biofilm-formation ability, rates of virulence gene carriage and antibiotic resistance were higher in isolates of S. pseudintermedius from dogs with bacterial keratitis compared with those isolated from healthy dogs [ 63 ]. Studies investigating the effect of NAC on these pathogenic bacterial strains causing corneal ulcerations are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The virulence of Staphylococcus pseudintermedius can be explained by several factors such as enzyme secretion (e.g., coagulase, thermonuclease, and proteases), toxin secretion (e.g., exfoliative toxin, enterotoxin, and cytotoxins) ( 28 ), and biofilm formation at the infection site ( 29 ). Specific to dogs with bacterial keratitis, a recent study showed that the biofilm-formation ability and rates of virulence gene carriage and antibiotic resistance were higher in the isolates of Staphylococcus pseudintermedius from dogs with keratitis compared with those from the healthy dogs ( 30 ). In humans, the reported detrimental effects of resistant strains include higher morbidity and mortality rates ( 31 ), limited antimicrobial treatment options for physicians, prolonged hospitalization times and increased healthcare costs ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…pseudintermedius (MRSP) ( 10–12 ). Furthermore, many MDRSP strains exhibit resistance to antimicrobial agents used in veterinary ophthalmology, such as fluoroquinolones and tetracyclines ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%